Perspektif Islam dan sains verterinar terhadap pemandulan kucing - Mohd Izhar Ariff Mohd Kashim,; Nur Asmadayana Hasim,; Loqman Mohamad Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The welfare of pets, especially cats, has always been a hot issue in Malaysia. This issue resulted from various crimes and cruelty to pets. For that reason, the legal view on the castration of pets like cats is the main interest of this article. In this study, the discussion on the law's determination involved veterinary scientists so that the decision is in line with animals' nature. Cat sterilisation is a method often practiced by cat lovers. However, this practice has become a subject of debate among scholars, veterinary scientists, and the public. Thus, this study aimed to determine the law of cat sterilization from the Islamic and veterinary science perspectives on the methods and effects of this sterilization procedure. This study used qualitative methods, literature highlights, and content analysis. Results showed that the Four Madhabs scholars have agreed that the pet sterilisation, such as cats, is makruh (disapproved). The Maqasid al-Shariah's concept revealed that cat sterilization could provide various benefits to humans and pets.